A APLICAÇÃO DE INSTRUMENTOS DE GARANTIA DE DIREITOS HUMANOS PARA AS MULHERES GRÁVIDAS E MÃES ENCARCERADAS NO BRASIL (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article aims to address how the application of Human Rights instruments occurs concerning the central group of this study, which is pregnant women and incarcerated mothers in the country. Through bibliographic and legal analyses, a discussion is held on which fundamental principles are violated when these women serve sentences in a prison system that is ill-equipped to accommodate them. As a means to prevent the mitigation of these rights, the government has been creating Human Rights protection instruments specifically tailored to women and their children. Thus, in order to ensure the realization of fundamental rights, legislative changes have been made in this regard; however, they are still recent and need to be correctly implemented, aiming for best for these individuals.